Diseño y Caracterización de Electrodos para la identificación de Sustancias Químicas en Medio Acuoso - Phillips-Brenes, Hayden (Instituto Tecnológico de Costa Rica, 2016)
The pollution of water resources has become a major concern of government and private organizations. Additionally, the gradual decline of this resource recall to protect water sources that are not contaminated and can be used for human consumption. However, the accelerated growing of population demanded to extend the farming fields, increasing the use of pesticides and herbicides. Therefore, the detection of contamination in water sources is requiring tools that allow “in situ” analysis, at reasonable costs and avoiding chemical methods that are harmful to the environment. This document describes the design, fabrication and characterization of a gold microelectrode coated with PEDOT polymer, for measuring concentrations contaminants that threaten water sources for human consumption and agricultural purposes. The capabilities of the electrode were verified by measuring the concentration of arsenic through cyclic-voltammetry technique, which allows to observe a specific peak of current for each concentration of arsenic. The experimental results indicated a maximum sensitivity of the electrode to a solution of arsenic in aqueous medium of 66.7 ug/L and a linear measurement range from 166.7 ug/L to 1000 ug/L. Furthermore, the measurement was simulated in COMSOL multi-physics package to compare the experimental results against theoretical results
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Contaminantes; Concentración; Difusión; Masa; Detección; Arsénico